USING POSSIBILITIES OF COMPUTER TECHNOLOGIES IN TEACHING THE SCIENCE OF ARCHITECTURE (Journal of Universal Science Research, 2024)
The article discusses the relevance of the use of computer technology in the teaching of special disciplines and the implementation of course projects, as well as the possibility of using these technologies.